A theoretical and experimental study to unequivocal structural assignment of tetrahydroquinoline derivatives - da Silva, Bruno Henrique Sacoman Torquato [UNESP]; Marana, Naiara Letícia [UNESP]; Mafud, Ana Carolina; da Silva-Filho, Luiz Carlos [UNESP] (Springer Nature, 2013)
The tetrahydroquinoline derivatives can be easily synthesized through Povarov reaction and have several important biological activities. This work describes a comparative study for the unequivocal assignment of molecular structure of different tetrahydroquinoline derivatives, through a complete analysis of NMR 1D and 2D NMR spectra (1H, 13C, COSY, HSQC, and HMBC), and the correlation this data with theoretical calculations of energy-minimization and chemical shift (δ), employing the theory level of DFT/B3LYP with set of the cc-pVDZ basis. For these derivatives the experimental analyses and the theoretical model adopted were sufficient to obtain a good description of its structures, and these results can be used to assign the structure of various others tetrahydroquinoline derivatives. © 2013 Springer Science+Business Media New York.
Keywords: Chemical shifts calculations; NMR; Poravov adducts; Tetrahydroquinoline derivatives; Theoretical study